The Role of Cdk5 and TRPV1 in Meloxicam Resistance Signal Transduction in Rat Experiencing Chronic Pain - Mohammad F. Qorib; Reny I’tishom; Sri A. Sudjarwo; Ahmad Basori (Indian Journal of Forensic Medicine & Toxicology, 2021)
Chronic pain is a common case and become a serious problem. Chronic pain management are inconclusive.One of the common treatment option is NSAID. Treatment Failed are around 34-79% of total case. Thesetreatment failed suspected as NSAID resistance. Treatment failed can be caused by a some molecule thatmake NSAID loss of efficacy. Cdk5 is one of the molecule that active in chronic pain condition. Cdk5 canincrease transmembrane insertion and activate TRPV1. The aim of this research is analyzed the role of cdk5and TRPV1 in NSAID resistance of chronic pain rat. This research used 42 rats as a subject and dividedinto 6 groups with random allocation method and factorial design. Meloxicam treatment was given orallyevery day for 7 days after rats have a chronic pain (28 days). Chronic pain induction used a CFA injection.Results : cdk5 and TRPV1 expression at the dorsal root ganglia of chronic pain groups are increase, nosignificant different of pain threshold and inflammation sign between treatment and no treatment groupsafter chronic pain occurred. Conclusion : chronic pain can induce cdk5 and TRPV1 expression, and inducedby meloxicam treatment. Cdk5 and TRPV1 have a positive correlation with meloxicam resistance.